Upaya Meningkatkan Kemampuan Bahasa Inggris Anak Kelompok B Dengan Menggunakan Strategi Pembelajaran Pesan Berantai Di TK Pertiwi III Sawahan, Ngemplak, Boyolali Tahun Pelajaran 2014/2015 - Putri, Paramita Desintya Purwityas; , Sri Slamet, M.Pd., M.Hum; , Wiji Astuti, s. Pd., M.Hum (2015)
Objective of this research is to know the strategy English study through the message related with child of group B TK Pertiwi III Sawahan, Ngemplak, Boyolali School Year 2014 / 2015. Before ability action read the low child English because method weared the teacher lose looks child. Solution which on the market in this research by using study order to related to. In action of researcher research used the card draw as according to study items. Subject research are child of group B TK Pertiwi III Sawahan, Ngemplak, Boyolali is 18 child. This research represent the research of class action. Technique data collecting use the observation method / perception, interview the, analysis of document and documentation. This research use 2 cycle, every cycle consisted of four step that is planning, execution, perception and reflection. Attainment indicator this research is 80% from indicator is determined. Result of research indicate that happened the increase in each cycle. This matter is marked from percentage of action pre is 46,6%, cycle I obtained 61,4%, and cycle II is 86,1%. Pursuant to result analyse the data, hypothesis expressing that: "By using study strategy order to related to can improve the ability of English child in TK Pertiwi III of group B Sawahan, Ngemplak, Boyolali" proven and acceptable its truth